Are ipRGCs involved in human color vision? Hints from physiology, psychophysics, and natural image statistics - Barrionuevo, Pablo Alejandro (2024)
Human photoreceptors consist of cones, rods, and melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs). First studied in circadian regulation and pupillary control, ipRGCs project to a variety of brain centers suggesting a broader involvement beyond non-visual functions. IpRGC responses are stable, long- lasting, and with a particular codification of photoreceptor signals. In comparison with the transient and adaptive nature of cone and rod signals, ipRGCs’ signaling might provide an ecological advantage to different attributes of color vision. Previous studies have indicated melanopsin’s influence on visual responses yet its contribution to color perception in humans remains debated. We summarized evidence and hypotheses (from physiology, psychophysics, and natural image statistics) about direct and indirect involvement of ipRGCs in human color vision, by first briefly assessing the current knowledge about the role of melanopsin and ipRGCs in vision and codification of spectral signals. We then approached the question about melanopsin activation eliciting a color percept, discussing studies using the silent substitution method. Finally, we explore various avenues through which ipRGCs might impact color perception indirectly, such as through involvement in peripheral color matching, post-receptoral pathways, color constancy, long-term chromatic adaptation, and chromatic induction. While there is consensus about the role of ipRGCs in brightness perception, confirming its direct contribution to human color perception requires further investigation. We proposed potential approaches for future research, emphasizing the need for empirical validation and methodological thoroughness to elucidate the exact role of ipRGCs in human color vision.